Implementasi Manajemen Mutu Terpadu pada Pendidikan Anak Usia Dini (Analisis di Play Group Taman Kanak-Kanak Islam Terpadu Harapan Mulia Palembang) - Sari, Maya Novita (Literasi: Jurnal Ilmu Pendidikan, 2017)
Quality education is a major requirement that must be met. Education should be given from an early age, because at that age should be grown to develop children's creativity. The problem is that many PAUD institutions fail to implement Total quality management. Where measures such as quality planing, quality control and quality importvment have not been optimized properly. Departing from that, it is interesting to see the extent to which the quality management is integrated when applied in the PAUD institution. This study aims to describe and analyze critically and to know the Implementation of TQM in PAUD institutions in Play Group IT Harapan Mulia Palembang. The approach used is descriptive qualitative, with data collection tool that is: observation, documentation, and interview. So found some findings in the research location that illustrates that the implementation of TQM in PAUD institutions become very necessary in supporting the quality of institutions, educators and students.Key Words ; Total Quality Management, Early Childhood Education and Development